Identification of potential therapeutic targets for systemic lupus erythematosus based on GEO database analysis and Mendelian randomization analysis - Apaer, Aishanjiang; Shi, Yanyan; Aobulitalifu, Alimijiang; Wen, Fujie; Muhetaer, Adalaiti; Ajimu, Nuermaimaiti; Sulitan, Maierhaba; Cheng, Lei (Frontiers in Genetics, 2024)
Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease. Current treatments mainly rely on immunosuppressants, which lack specificity and pose challenges during treatment. This study aims to deeply explore the molecular pathogenic mechanism of SLE through gene expression databases (GEO) and bioinformatics analysis methods, combined with Mendelian randomization analysis, to provide key clues for new therapeutic targets.